Inhibitory Effects Of Andrographolide In Pc-3 Cell Line And The Induction Of Apoptosis Via The Involvement Of Caspases 3, 8 And 9 - Manimaran, Janany (2023)
Andrographolide is a labdane diterpenoid isolated from the plant Andrographis paniculata. This substance has numerous medicinal uses, notably anticancer effects. A previous study has revealed that andrographolide inhibits the growth of lung, brain, colon, and breast cancer cells. Due to a lack of research, the knowledge of andrographolide's anti-cancer effects on prostate cancer cells is relatively poor. In the current study, andrographolide was assessed on PC-3 cells, an aggressive androgen-independent prostate cancer cell line. Cytotoxicity analysis is vital in drug discovery research for assessing the biocompatibility of the drug being used on cancer cells. This work used the WST-1 assay to determine the cell survival of PC-3 cancer cells and Hs27 normal cells exposed to varying doses of andrographolide (0-200 μM). The results indicate that andrographolide dose-dependently suppresses the viability of PC-3 cells but not Hs27 cells. The NCI considers the LC50 value of 26.42 μM (after 48 hours of incubation) is acceptable. For the first time in this study, three different concentrations of andrographolide were used: control, half LC50, and LC50 (0, 13.21, and 26.42 μM) in all subsequent analyses. Metastasis is essential for the disease to progress; hence, the scratch assay and the transwell invasion assay were used to test andrographolide on PC-3 cells.